Arnica montana Cell Culture Establishment, and Assessment of Its Cytotoxic, Antibacterial, α-Amylase Inhibitor, and Antioxidant In Vitro Bioactivities - Aurelio Nieto-Trujillo (MDPI AG, 2021)
Arnica montana cell suspension culture could be a sustainable source of a vegetal material producer of secondary metabolites (SMs) possessing biological effects. Different plant growth regulator concentrations (0–5 mg/L) were tested in foliar explants to induce a callus that was used to establish a cell suspension culture. Growth kinetics was carried out for 30 days. A methanolic extract obtained from biomass harvested at 30 days of growth kinetics was fractionated, and three fractions were tested for bioactivities. We induced a callus with 1 mg/L of picloram and 0.5 mg/L of kinetin in foliar explants, which allowed for the establishment of a cell suspension culture, and the latter had the highest total SMs contents at day 30. Three fractions showed differences in total SMs contents, with the highest values per gram as follows: 270 mg gallic acid equivalent for total phenolic content, 200 mg quercetin equivalent for total flavonoid content, 83 mg verbascoside equivalent for total phenolic acid content, and 396 mg parthenolide equivalent for total sesquiterpene lactone content. The best bioactivities were 2–6 µg/mL for the 50% inhibition of 2,2-diphenyl-1-picrylhydrazyl radical, 30% cellular viability of lymphoma cells at 40 µg/mL, 17% inhibition against Escherichia coli and Staphylococcus aureus at 8 µg/disk, and α-amylase inhibition at 12% with 10 µg/mL. The total SMs contents were correlated with bioactivities.